Providing Appropriate PKH Assistence To Communities In Klambir Lima - Yusman, Yanti; Putri, Ranti Eka; Amelia, Loli (International Conference on Sciences Development and Technology, 2022)
The village of klambir lima kebun is a village in one of the villages subdistrict silver exspance deli serdang regency, north sumatra province the family hope program (PKH) is a goverment program in which the village of klambir lima is experiencing difficulties in determining who is eligible to reiceve assistence. Therefore the authors are interested in conducting research to provide assistence in making desicions thet can overcome existiing problems so that the selection procces for prospective recipients of the family hope program (PKH) can be produced precisely and accurately. The hope family program, whitch will be called PKH is a program provision of social assistance to the poor who remain as a family PKH beneficiaries. As poverty allevition since 2007 the goverbment indonesia has implemented the PKH social peotection progrom whict is aslo known in the international community with the term conditional  cast transfers ( CTT ) is sufficient faced by these countries especially the problem of chronic poverty. As a conditional social assistance program PKH opens access for poor famies, especially pregnant women and children school to take advantage of varios health service facilities ( fankes ) and facilites educationl service ( fasdik ) aveilable around them also benefit from PKH initially encoraged to include person with disabilities and the elderly with maintaining the level of social welfare in accordance with the mandate of the constitution an nawacita